Partial Substitution of Binding Material by Bentonite Clay (BC) in Concrete: A Review - Jawad Ahmad; Karolos J. Kontoleon; Mohammed Zuhear Al-Mulali; Saboor Shaik; Mohamed Hechmi El Ouni; Mohammed A. El-Shorbagy (Buildings, 2022)
Concrete consumes millions of tons of cement, which causes global warming as cement factories emit huge amounts of carbon dioxide into the atmosphere. Thus, it is essential to explore alternative materials as a substitute of OPC, which are eco-friendly and at the same time cost-effective. Although there are different options available to use industrial waste instead of cement, such as waste glass, waste marble, silica fume fly ash, or agriculture waste such as rice husk ash, wheat straw ash, etc., but bentonite clay is also one of the best options to be used as a binding material. There are a lot of diverse opinions regarding the use of bentonite clay as a cement substitute, but this knowledge is scattered, and no one can easily judge the suitability of bentonite clay as a binding material. Accordingly, a compressive review is essential to explore the suitability of bentonite clay as a cementitious material. This review focuses on the appropriateness of bentonite clay as a binding material in concrete production. The attention of this review is to discuss the physical and chemical composition of BC and the impact of BC on the fresh and mechanical performance of concrete. Furthermore, durability performance such as water absorption, acid resistance and dry shrinkage are also discussed. The results indicate that bentonite clay increased the mechanical and durability performance of concrete up to some extent but decrease its flowability. The optimum proportion of bentonite clay varies from 15 to 20% depending on the source of bentonite clay. The overall study demonstrates that bentonite clay has the creditability to be utilized partially instead of cement in concrete.